Safety and efficacy of sugammadex in management of patients with myasthenia gravis undergoing general anesthesia: A systematic review - Alan D. Kaye; Emily A. Villafarra; Erin S. Everett; Erin E. Ware; Sydney A. Mashaw; William D. Brouillette; Camille G. Elder; Taylor Moss; Luke Muiznieks; Edwin Herron; Shahab Ahmadzadeh; Sahar Shekoohi (Heliyon)
Objective: The objective of this study was to analyze available evidence on efficacy and safety of sugammadex in reversing neuromuscular blockades in patients with Myasthenia Gravis (MG), thereby providing a comprehensive understanding of its potential benefits and risks in this specific patient population. Methods: We performed a systematic search for studies from PubMed, Embase, Web of Science, and Google Scholar. Sources were screened using Rayyan, following predefined inclusion and exclusion criteria focusing on English articles published from 2010 to 2024 on MG patients under general anesthesia. Data on patient characteristics and outcomes were extracted, and quality was appraised using the JBI Critical Appraisal Checklist. Results: Out of 361 initial citations, 24 studies met inclusion criteria. Sugammadex demonstrated rapid and effective reversal of neuromuscular blockades, with ToF recovery times ranging from 79.7 s to 10 min, and short extubation times. The incidence of postoperative myasthenic crisis was low, and no mortalities were reported. Conclusion: Sugammadex may serve as a reasonable option for the reversal of neuromuscular blockades in MG patients, indicating potential for rapid recovery and a relatively low incidence of serious complications. However, due to the limited number of studies and the nature of the evidence available, further large-scale and rigorous investigations are warranted to better establish its superiority over traditional reversal agents.